2009
DOI: 10.1097/01.ogx.0000363238.87643.57
|View full text |Cite
|
Sign up to set email alerts
|

Hormone Therapy and Ovarian Cancer

Abstract: The use of synthetic mesh to augment vaginal repair procedures for pelvic organ prolapse has increased in large part because of dissatisfaction with the success rates of traditional colporrhaphy. Its use, however, is controversial. Four randomized controlled studies comparing traditional colporrhaphy with vaginal repair using mesh augmentation had conflicting results. This unblinded, prospective, randomized controlled trial investigated whether mesh augmentation during vaginal repair would reduce the rate of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
31
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(43 citation statements)
references
References 0 publications
9
31
3
Order By: Relevance
“…It is difficult to determine whether this reflects a real similarity in associations by constituent, regimen, and route of administration or a lack of statistical power based on small numbers in these subgroups. However, our findings are consistent with data from other large prospective studies [11,12,14,16].…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…It is difficult to determine whether this reflects a real similarity in associations by constituent, regimen, and route of administration or a lack of statistical power based on small numbers in these subgroups. However, our findings are consistent with data from other large prospective studies [11,12,14,16].…”
Section: Discussionsupporting
confidence: 93%
“…These findings are consistent with other prospective studies that have reported increased risks of between 25 and 107% for estrogen-only use and ovarian cancer risk [10][11][12][13][14][15][16]. The evidence for an association with use of estrogen plus progestin therapy is less consistent; most case-control studies have found no association [17- 23], while some [11,14,16], but not all prospective studies have reported small increased risks [10,12,13,15]. The Women's Health Initiative trial found a non-significant 58% higher risk (95% CI, 0.77-3.24) for estrogen plus progestin HT, based on 32 cases of ovarian cancer during an average of 5.6 years of follow-up [24].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Recently, it has been suggested that the risk is increased irrespective of the type of HT [3,4]. However, a differential risk between combined HT and estrogen-only therapy has also been suggested.…”
Section: Introductionmentioning
confidence: 99%